DISASTER DISPLACEMENT AND HUMAN RIGHTS: INVESTIGATING THE ROLE OF INTERNATIONAL LAW (Archive of Conferences, 2021)
Due to the record-breaking number of people affected by disasters, this article looks at how international law applies to disaster displacement, why refugee law is unlikely to be the solution, and how it can apply it to current developments in contemporary situations. It also discusses how can apply recent developments in contemporary situations. Disaster planning and preparedness are now explicitly included in nations' international legal obligations due to new interpretations of international human rights law. Furthermore, due to global warming, disasters like flooding and drought will occur more frequently and with greater intensity, complicating the implementation of international humanitarian law. As national governments restrict borders, anti-immigrant sentiment grows, and economies decline, further "othering" of migrants could make it more difficult to put protections in place.